2008
DOI: 10.1007/s11230-008-9159-1
|View full text |Cite
|
Sign up to set email alerts
|

Monogeneans of the grouper Epinephelus tauvina (Perciformes, Serranidae) off Moorea, French Polynesia, with a description of Pseudorhabdosynochus pai n. sp. (Monogenea: Diplectanidae)

Abstract: Specimens of the greasy grouper Epinephelus tauvina (Forsskål), caught off Moorea, French Polynesia, harboured four species of gill monogeneans. The diplectanid Pseudorhabdosynochus pai n. sp. is characterised by an extremely big male quadriloculate organ (inner length 77 mum, cone length 15, tube length 47), the largest of all members of the genus, and a sclerotised vagina with a very complex structure, including three secondary chambers instead of one as in most species. Pseudorhabdosynochus sp. is a species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…After this date, 25 more species were described. The species of Pseudorhabdosynochus mostly parasitize fish belonging to Epinephelus and have been described from different regions of the world [ 1 , 2 , 6 – 12 , 17 , 19 – 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…After this date, 25 more species were described. The species of Pseudorhabdosynochus mostly parasitize fish belonging to Epinephelus and have been described from different regions of the world [ 1 , 2 , 6 – 12 , 17 , 19 – 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another hypothesis is that the three species of Mycteroperca with similar species of Pseudorhabdosynochus are all from the Mediterranean Sea (and Eastern Atlantic), suggesting that the close relationships of these parasite species reflect a common geographical origin, with the differentiation of various monogenean species in the groupers from the same area. However, a similar vaginal structure is found in P. pai , a parasite of Epinephelus tauvina in the Pacific [ 24 ] (i.e. neither a species of Mycteroperca nor Mediterranean), thus negating the two hypotheses mentioned above.…”
Section: Discussionmentioning
confidence: 67%
“…The general structure is similar, but the primary canal is shorter in P. regius and the shape of the secondary chamber is different and complex (i.e. several secondary chambers) [ 24 ]. In addition, P. pai has a huge quadriloculate organ (72–144 inner length) and larger squamodiscs with numerous rows of rodlets (13–14).…”
Section: Pseudorhabdosynochus Regius N Spmentioning
confidence: 99%
“…They found that several species of the cupatus group were found in several Epinephelus spp., and that these fish species were related. Recent descriptions of new species confirm that a monophyletic group of groupers (Craig and Hastings 2007) harbours a series of Pseudorhabdosynochus of the cupatus group, and also other species (Justine 2008, Justine andVignon 2009).…”
Section: Discussionmentioning
confidence: 94%